Assembly-enhanced recognition: A biomimetic pathway to achieve ultrahigh affinities - Fang-Yuan Chen; Wen-Chao Geng; Meng-Meng Chen; Rong Fu; Han Han; Zhan-Zhan Zhang; Wen-Bo Li; Yuan-Qiu Cheng; Juan-Juan Li; J. Fraser Stoddart; Kang Cai; Dong-Sheng Guo (Proceedings of the National Academy of Sciences, 2025)
On the one hand, nature utilizes hierarchical assemblies to create complex biological binding pockets, enabling ultrastrong recognition toward substrates in aqueous solutions. On the other hand, chemists have been fervently pursuing high-affinity recognition by constructing covalently well-preorganized stereoelectronic cavities. The potential of noncovalent assembly, however, for enhancing molecular recognition has long been underestimated. Inspired by (strept)avidin, an amphiphilic azocalix[4]arene derivative capable of assembly in aqueous solutions has been explored by us and demonstrated to exhibit ultrahigh binding affinity (up to 10 12 M −1 ), which is almost four orders of magnitude higher than those reported for nonassembled azocalix[4]arenes. An ultrastable azocalix[4]arene/photosensitizer complex has been applied in hypoxia-targeted photodynamic therapy for tumors. These findings highlight the immense potential of an assembly-enhanced recognition strategy in the development of the next generation of artificial receptors with appropriate functionalities and extraordinary recognition properties.